#### Answer

Therefore $f^{-1}(f(6))$ = 6

#### Work Step by Step

Since the function is one-to-one, remember that $f^{-1}(f(x))$ = x. Therefore $f^{-1}(f(6))$ = 6

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

Therefore $f^{-1}(f(6))$ = 6

Since the function is one-to-one, remember that $f^{-1}(f(x))$ = x. Therefore $f^{-1}(f(6))$ = 6

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.